An ex-vivo study on the shaping parameters of two nickel-titanium rotary systems compared with hand instruments - Ehsani, Maryam; Zahedpasha, Samir; Moghadamnia, Ali-Akbar; Mirjani, Jaber (Iranian Endodontic Journal, 2011)
INTRODUCTION: Rotary nickel-titanium (NiTi) instruments are thought to allow shaping of narrow, curved root canals more efficiently and more effectively than stainless steel hand instruments. However, the continued search for even more effective and safer instruments has resulted in new rotary systems being introduced on a regular basis. The aim of this study was to compare shaping parameters of RaCe and Mtwo NiTi rotary files with stainless steel K-Flexofile hand instrument. MATERIALS & METHODS: A total of 60 mandibular first molars with 20-40 degree of curvature in mesial root were divided in to three groups and each was prepared with one kind of instrument (RaCe, Mtwo, stainless steel K-Flexofile). Using pre and post-radiographs, canal curvature was measured, with the Schneider technique. Preparation time was recorded. For evaluating canal centering and transportation, the tooth was sectioned 3, 6 and 9 mm from the apex. Pre and post- preparation photographs were taken from mesiolingual canal. Data was statistically analyzed using One-way ANOVA and Chi-Square tests. RESULTS: RaCe and Mtwo maintained canal curvature better than K-Flexofile (P<0.001). Mtwo prepared the canal in a shorter time (P<0.001). CONCLUSION: Significant statistical difference was not found in the three canal sections between the various systems. RaCe resulted in significantly fewer canal aberrations and better centering ability.